Supreme leadership in modern war
1 online resource.
Keywords: "This edited volume focuses on civil-military relations before and during great power conflicts, and comprises historical case studies of modern supreme leadership. It aims to provide a guide for the future by shining a light on what worked and what failed in the civil-military relationships that steered great powers during the last era of rapid global change. While future civil-military relationships will have to adapt to the current global environment, the past remains, as always, a prelude. Thus, crucial concepts that underpin all such relationships are eternal and are waiting to be drawn out by historians trained to examine and present them to those who can put them to immediate good use. This volume demonstrates the relevance of history in every chapter, as readers will see parallels to today's problems throughout every case study. The world is entering an age of great challenges, many of which require nations - particularly the most powerful - to establish civil-military relationships capable of navigating dangerous currents without a repeat of the calamities reminiscent of the last century. Each chapter focuses on a particular civil-military relationship as it developed before and during a great war. The editors have gathered leading experts on each of these periods to produce a concise but thorough essay on each relationship's intricacies. This book will be of much interest to students of military and strategic studies, military history and International Relations, as well as professional miliary colleges and policymakers"--